Influence of welding processes for underground pipeline repair on welder safety - Vasyliv, Nataliia; Semchuk, Yaroslav (Technology audit and production reserves, 2019)
The object of research is the welder safety during the repair and construction of underground pipelines. It is established that manual electric welding is characterized by significant influence on the human body, since the distance from the place of welding to the welder is 20–30 cm, the temperature in the pillar of the welding arc reaches 6500 K. It is contributes to the allocation in the surrounding space of a significant amount of metal vapor and fine particles (welding aerosol and toxic gases). Theoretical and experimental investigations of the initial part of the welding torch (at a height of 0.4–0.5 m) using manual, semi-automatic welding in the environment of protective gases and welding under a layer of flux have been carried out. Dependencies for determining axial temperatures and velocities are proposed. It is substantiated that the spreading of aerosols during welding of pipelines in the trench is determined by the physical processes of spreading the welding torch. The hygienic characteristics of the electrodes of the ANO type in the welding processes are investigated. It is established that the total amount of aerosol in the process of welding using ANO-4 electrodes with basic coating reaches 31 g/kg and toxic substances in aerosol up to 9 g/kg. The amount of gases in front of the welder shield during the welding of electrodes by ANO-8 reaches 20 mg/m3. Empirical equations for determination of aerosols concentration and gaseous concentration of harmful substances are obtained. In addition, an equation for determining the index of workplace pollution of welders, which made it possible to predict individual parameters of working conditions, is obtained. The mechanism of propagation of aerosols in the trench requires a special consideration, which can be carried out by the method of mathematical modeling, because such physical and chemical processes, as longitudinal and transverse dispersion, molecular diffusion play a role. The analysis of empirical formulas which can be recommended for determination of parameters in the initial section of a welding torch using flash welding of a pipeline in a trench is done.